Contribution of Al-Muslimin Mosque Youth in Fostering Religious Attitudes in the Gerilya Road Community - Arlina; Desi Sabtina; Arif Rahman Hakim; Arif Rio Kari; Amalia Nurhanisah (al-Afkar, Journal For Islamic Studies, 2025)
In the teachings of the Islamic religion, a person's religiousness can not only be realized through ritual activities, but also seen from several other views. Among them, in terms of faith, this is characterized by a strong belief in a person's heart that Allah is his God. Religious values ​​have a very important role in human life, because in every religion there are values ​​that serve as guidelines for society, nation and state. A religious attitude can encourage individuals to have a strong moral framework, find meaning in life, and feel connected to something bigger than themselves. The importance of these religious values ​​has been recognized in various studies. This research approach is to use qualitative research, data presented in the form of verbal words, not in the form of numbers. In this research, primary data was obtained from interviews with the community around the mosque and also interviews with teenagers from the Al-Muslimin mosque. . Secondary data in research is documentation that the author collected during the observation process. Tadarus Al-Quran in the month of Ramadhan. In filling and honoring the holy month of Ramadhan, teenagers are accustomed to reading the Al-Qur'an. Maghrib Reciting the Koran At the end of every evening, Monday - Friday, teenagers from the Al-Muslimin Mosque teach children in the area around the Muslimin mosque. Fajr study is carried out once a week, Reading Yasin, Tahtim every Friday.